A new method for evaluation of fracture network formation capacity of rock. (15th January 2015) - Guo, Tiankui; Zhang, Shicheng; Ge, Hongkui; Wang, Xiaoqiong; Lei, Xin; Xiao, Bo
Highlights: A new method for evaluation of fracture network formation capacity is developed. Acoustic emission location is used for dynamic monitoring of SCA fracturing. Three commonly used brittleness evaluation methods are analysed. Fracture is characterized by using fractal dimension of the trace and areal density. Abstract: An effective evaluation on fracture network forming capacity is key to the whole process of shale gas exploration. At present, neither a clear standard nor a generally accepted evaluation method exist. In this study, a novel "Soundless Cracking Agent (SCA) fracturing evaluation method" was developed. The fractures were characterized quantitatively using fractal dimension of the trace on the core surface and areal density. Acoustic emission (AE) location was used for dynamic monitoring and analysis. The results show that the fractal dimension can be used for quantitative evaluation of complexity of fracture network. The higher the rock hardness, the smaller the fracture density after fracturing is; the higher the brittleness, the larger the fracture density after fracturing is. The development degree of natural fracture systems and sedimentary bedding is a key factor to control the propagating morphology of fractures. The number of AE events for sandstones with low clay content (<25%) is huge, and there are obvious take-off spots for cumulative curves and frequency distribution curves. The AE events for sandstones are distributed along the main fractures, with simple planar fractures clearly present after fracturing. But for shale, the number of AE events is less, with no obvious take-off spots, and AE events are scatteredly distributed. The higher the clay content and the lower the quartz content, the smaller the number of AE events is, and the smaller the frequency and the sound source amplitude are. For sandstone, the number of AE events decreased by about 75% due to the increase of clay content by 20%. The new method enables a comprehensive reflection of the characteristics of rock hardness, brittleness and natural fractures system. This work is valuable for the evaluation of hydraulic fracturing effects in unconventional oil and gas reservoirs in the future.